Concorde : The Rise and Fall of the Supersonic Airliner - Glancey, Jonathan (London Atlantic Books, 2015)
Concorde tells the story of this magnificent and hugely popular aircraft anew, taking the reader from the moment Captain Chuck Yeager first broke the sound barrier in 1947 through to the last commercial flight of the supersonic airliner in 2003. It is a tale of national rivalries, technological leaps, daring prototypes, tightrope politics, and a dream of a Dan Dare future never quite realized. This is a celebration, as well as a thoroughly researched history, of a truly brilliant machine that became a sky god of its era." --Back cover of book
Include Illustrations and Index